Plastic Plants: The Role of Water Hyacinths in Plastic Transport in Tropical Rivers - Schreyers, Louise; van Emmerik, Tim; Nguyen, Thanh Luan; Castrop, Evelien; Phung, Ngoc-Anh; Kieu-Le, Thuy-Chung; Strady, Emilie; Biermann, Lauren; van der Ploeg, Martine (Frontiers in Environmental Science, 2021)
Recent studies suggest that water hyacinths can influence the transport of macroplastics in freshwater ecosystems at tropical latitudes. Forming large patches of several meters at the water surface, water hyacinths can entrain and aggregate large amounts of floating debris, including plastic items. Research on this topic is still novel and few studies have quantified the role of the water hyacinths in plastic transport. In this study, we present the findings of a six-week monitoring campaign, combining the use of visual observations and UAV imagery in the Saigon river, Vietnam. For the first time, we provide observational evidence that the majority of macroplastic is transported by water hyacinth patches. Over the study period, these fast-growing and free-floating water plants transported 78% of the macroplastics observed. Additionally, we present insights on the spatial distribution of plastic and hyacinths across the river width, and the different characteristics of entrapped items compared with free-floating ones. With this study, we demonstrate the role of water hyacinths as a river plastic aggregator, which is crucial for improving the understanding of plastic transport, and optimizing future monitoring and collection strategies.